Trehalase Inhibitor Validamycin May Have Additional Mechanisms of Toxicology against Rhizoctonia cerealis - Xiaoyue Yang; Yan Shu; Shulin Cao; Haiyan Sun; Xin Zhang; Aixiang Zhang; Yan Li; Dongfang Ma; Huaigu Chen; Wei Li (Journal of Fungi, 2023)
Sharp eyespot is a crucial disease affecting cereal plants, such as bread wheat (Triticum aestivum) and barley (Hordeum vulgare), and is primarily caused by the pathogenic fungus Rhizoctonia cerealis. As disease severity has increased, it has become imperative to find an effective and reasonable control strategy. One such strategy is the use of the trehalose analog, validamycin, which has been shown to have a potent inhibitory effect on several trehalases found in both insects and fungi, and is widely used as a fungicide in agriculture. In this study, we demonstrated that 0.5 μg/mL validamycin on PDA plates had an inhibitory effect on R. cerealis strain R0301, but had no significant impact on Fusarium graminearum strain PH-1. Except for its inhibiting the trehalase activity of pathogenic fungi, little is known about its mechanism of action. Six trehalase genes were identified in the genome of R. cerealis, including one neutral trehalase and five acidic trehalase genes. Enzyme activity assays indicated that treatment with 5 μg/mL validamycin significantly reduces trehalase activity, providing evidence that validamycin treatment does indeed affect trehalase, even though the expression levels of most trehalase genes, except Rc17406, were not obviously affected. Transcriptome analysis revealed that treatment with validamycin downregulated genes involved in metabolic processes, ribosome biogenesis, and pathogenicity in the R. cerealis. KEGG pathway analysis further showed that validamycin affected genes related to the MAPK signaling pathway, with a significant decrease in ribosome synthesis and assembly. In conclusion, our results indicated that validamycin not only inhibits trehalose activity, but also affects the ribosome synthesis and MAPK pathways of R. cerealis, leading to the suppression of fungal growth and pesticidal effects. This study provides novel insights into the mechanism of action of validamycin.